2017
DOI: 10.1155/2017/5260106
|View full text |Cite
|
Sign up to set email alerts
|

Addition of Wollastonite Fibers to Calcium Phosphate Cement Increases Cell Viability and Stimulates Differentiation of Osteoblast-Like Cells

Abstract: Calcium phosphate cement (CPC) that is based on α-tricalcium phosphate (α-TCP) is considered desirable for bone tissue engineering because of its relatively rapid degradation properties. However, such cement is relatively weak, restricting its use to areas of low mechanical stress. Wollastonite fibers (WF) have been used to improve the mechanical strength of biomaterials. However, the biological properties of WF remain poorly understood. Here, we tested the response of osteoblast-like cells to being cultured o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 34 publications
2
8
0
1
Order By: Relevance
“…The mechanism and characteristics of the interaction of structural component, and the phase of bone tissue neoplasm using silicates are given in the review [ 42 , 43 ]. At the same time, the presence of silicates in the bone tissue suppressed the activity of osteoclasts [ 44 , 45 ], which agreed with the authors’ observations in the present study.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…The mechanism and characteristics of the interaction of structural component, and the phase of bone tissue neoplasm using silicates are given in the review [ 42 , 43 ]. At the same time, the presence of silicates in the bone tissue suppressed the activity of osteoclasts [ 44 , 45 ], which agreed with the authors’ observations in the present study.…”
Section: Resultssupporting
confidence: 93%
“…The mechanism and characteristics of the interaction of structural component, and the phase of bone tissue neoplasm using silicates are given in the review [42,43]. At the same time, the presence of silicates in the bone tissue suppressed the activity of osteoclasts [44,45], which agreed with the authors' observations in the present study. The morphometric study of the components of bone tissue in the area of implantation and the control samples showed that the number of osteoblasts in the area of implantation per 1 mm 2 was significantly higher than in the control area, and was equal to 1.6 ± 0.12 vs. 1.1 ± 0.1.…”
Section: Resultssupporting
confidence: 91%
“…Moreover, CPC is hydrolyzed when in contact with the solution, giving rise to a layer of biological apatite that enables binding to bone tissue, thus improving graft assimilation. 36 The cell viability of pol5 and pol10 was similar to that of mβ-TCP, suggesting that poloxamer did not have a negative effect in MC3T3-E1 cells. Namely poloxamer is not significantly cytotoxic to the cells under the tested conditions.…”
Section: Discussionmentioning
confidence: 83%
“…In vitro study of biomaterials in cell culture is an important mechanism for determining how materials react at the cellular level. 36 Suitable biomaterials should have a non-cytotoxic response and support osteoblastic differentiation. 37 In this study, we evaluated the response of cultured osteoblast-like cells to poloxamer-added CPC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation